1994
DOI: 10.3386/w4811
|View full text |Cite
|
Sign up to set email alerts
|

The Intertemporal Allocation of Consumption: Theory and Evidence

Abstract: Liquidity constraints and, more generally, imperfections in credit markets, can be extremely important for the interteinporal allocation of consumption and have received a substantial amount of attention in the theoretical and empirical literature on consumption. In the first part of the paper I review the reasons why liquidity constraints are important.Unfortunately, for several reasons, it is not easy to test for the presence of liquidity constraints. Aggregation issues preclude the use of aggregate time ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Section (Flavin, 1985; Hubbard and ee Galf (1990), Attanasio and Weber (1993), Goodfriend (1992), and Pischke (1995). Judd, 1986;Hayashi, 1987 (Browning, 1991; see also Attanasio, 1995, for discussion) 2 intertemporal dependence originating from the preference side has vastly different policy implications than credit constraints.…”
mentioning
confidence: 99%
“…Section (Flavin, 1985; Hubbard and ee Galf (1990), Attanasio and Weber (1993), Goodfriend (1992), and Pischke (1995). Judd, 1986;Hayashi, 1987 (Browning, 1991; see also Attanasio, 1995, for discussion) 2 intertemporal dependence originating from the preference side has vastly different policy implications than credit constraints.…”
mentioning
confidence: 99%
“…The resulting income profiles are similar to those used in Attanasio (1995), Carroll and Summers (1991), and Gourinchas and Parker (1996). They are plotted in figure 11.1, along with the underlying age dummies for each of the three education groups.…”
Section: The Labor Income Processmentioning
confidence: 67%
“…To control for education, the sample is split into three groups: households without high school education, a second group with high school education but without a college degree, and, finally, college graduates. This sample split is intended to accommodate the well-established finding that age profiles differ in shape across education groups (Attanasio 1995;Hubbard, Skinner, and Zeldes 1994). For each education group, the function f (t, Z it ) is assumed to be additively separable in t and Z it .…”
Section: The Labor Income Processmentioning
confidence: 99%
“…Pratap (forthcoming) shows that this result is consistent with the presence of liquidity constraints when capital adjustment costs are non-convex. 3 See for example, Whited (1992) and Kwon (1994) for this result in US firm data in the manufacturing and retail sector respectively. Similar results have been obtained for firm level data in the U.K. (Bond & Meghir 1994) and Canada (Ng & Schaller 1996) and aggregate data in the U.S. (Gertler, Hubbard & Kashyap 1991 of firm investment.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies find that the restriction is strongly rejected for firms which have been identified as constrained. 3 Although this method can circumvent the problems associated with the measurement of q, it suffers from some of the same drawbacks. The rejection of a null hypothesis of a specific investment model without liquidity constraints does not give us any information on what an alternative model should be.…”
Section: Introductionmentioning
confidence: 99%